2018
DOI: 10.4132/jptm.2017.10.20
|View full text |Cite
|
Sign up to set email alerts
|

The Smad4/PTEN Expression Pattern Predicts Clinical Outcomes in Colorectal Adenocarcinoma

Abstract: Background Smad4 and PTEN are prognostic indicators for various tumor types. Smad4 regulates tumor suppression, whereas PTEN inhibits cell proliferation. We analyzed and compared the performance of Smad4 and PTEN for predicting the prognosis of patients with colorectal adenocarcinoma. Methods Combined expression patterns based on Smad4+/– and PTEN+/– status were evaluated by immunostaining using a tissue microarray of colorectal adenocarcinoma. The relationships between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 39 publications
1
15
1
Order By: Relevance
“…As a result, 16.4% of our cases were identified as SMAD4 loss, which falls within the range of previous reports. Consistent with the previous studies, [8][9][10][11][12][13][14][15][16][17] we observed a significant association between SMAD4 loss and higher pT and pN category, and frequent distant metastasis. Consequently, we confirmed the value of SMAD4 loss as a prognostic factor for poor CSS and PFS of CRC.…”
Section: Prognostic Implication Of Smad4 Loss In Crcssupporting
confidence: 92%
See 3 more Smart Citations
“…As a result, 16.4% of our cases were identified as SMAD4 loss, which falls within the range of previous reports. Consistent with the previous studies, [8][9][10][11][12][13][14][15][16][17] we observed a significant association between SMAD4 loss and higher pT and pN category, and frequent distant metastasis. Consequently, we confirmed the value of SMAD4 loss as a prognostic factor for poor CSS and PFS of CRC.…”
Section: Prognostic Implication Of Smad4 Loss In Crcssupporting
confidence: 92%
“…Most previous studies evaluated SMAD4 expression based on two-tier classification: loss versus no loss, or low versus high expression. 7,8,10,11,[13][14][15]17,18,20 Because of ambiguities in the definition of low expression, the reported prevalence of low-level SMAD4 expression varied significantly from 2.34% to 75.2%. On the other hand, studies that adopted a multi-tier classifica-tion reported relatively homogeneous results, with the prevalence of low-level SMAD4 expression ranging from 9.3% to 37.7%.…”
Section: Prognostic Implication Of Smad4 Loss In Crcsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reports from Chung et al from 2018 show that the loss of the SMAD4 protein together with the PTEN protein has a synergistic effect leading to a more aggressive form of the disease and an unfavourable prognosis in patients with CRC compared to the loss of SMAD4 alone [37].…”
Section: Smad4 Genementioning
confidence: 99%